Characteristics of Newly Diagnosed Hepatocellular Carcinoma Patients Across Turkey: Prospective Multicenter Observational 3K Registry Study - Dinc Dincer 0,; on behalf of K Registry Study Group,; Ramazan Idilman,; Zeynep Merve Cevik,; Arzu Baygul,; Ozgur Ozyilkan,; Canan Alkım,; Hakan Akbulut,; Idris Yucel,; Salim Basol Tekin,; Ulus Salih Akarca,; Abdullah Sonsuz,; et al. (Turkish Journal of Gastroenterology, 2021)
Aims: To evaluate patient profile for epidemiological and clinicopathological characteristics and potential risk/prognostic factors in newly diagnosed hepatocellular carcinoma (HCC) patients across Turkey. Methods: A total of 547 patients (mean (SD) age 62.6 (10.3) years, 81.9% were males) were included in this registry study. Data on patient characteristics, etiologies of HCC, laboratory values, and tumor characteristics and stages were recorded at study enrollment. Results: HBV infection (68.2%) was the leading etiology, followed by HCV infection (17.2%), HDV infection (5.5%), alcohol (6.4%), and NAFLD (3.5%), as the major etiologies. Considering that 51.6% of the patients had >5 cm HCC, 44% were Child–Pugh B/C and 57% were BCLC B-D, it appears that a significant group of HCC patients were diagnosed at advanced stages. Of 540 patients, 271 (50.2%) were referred or applied with the diagnosis of HCC. Patients with HCC at presentation had larger tumor size (median (min-max) 6.6 (0-30) vs. 4.8 (0-90) cm, P < .001) and more advanced BCLC stage (Stage C-D in 40.8% vs. 26.4%, respectively, P = .005), compared to patients who were diagnosed during follow-up. Conclusions: Our findings revealed that HBV infection was the leading etiology and a moderate-to-advanced disease was evident in more than half of patients at the time of diagnosis. HCC patients diagnosed at follow-up had smaller tumor size and earlier BCLC stage. Cite this article as: Salih Akarca U, Unsal B, Sezgin O, et al. Characteristics of newly diagnosed hepatocellular carcinoma patients across turkey: prospective multicenter observational 3K registry study. Turk J Gastroenterol. 2021;32(12):1019-1028.